Cyber crime vs cyber security: implications for customer trust in e-banking at Indonesian Islamic banks - Ubay Harun; Muthmainnah; Rizki Amalia (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
This study explores the impact of cybercrime and cybersecurity on customer trust in e-banking services at Bank Syariah Indonesia (BSI), Palu Gajah Mada Branch, addressing a research gap related to the limited studies in the Islamic banking sector. The study offers a novel approach by integrating sharia principles into the analysis of digital security. The aim of this research is to identify how cyber threats and cybersecurity measures influence customers’ perceptions of e-banking security. Using a quantitative approach with a correlational design, the study involved 100 respondents selected through an accidental sampling method. The results of linear regression analysis indicate that cybercrime significantly reduces customer trust, while cybersecurity has a strong positive influence. The implications of these findings highlight the need for increased investment in digital security to maintain customer trust, ultimately supporting the stability and growth of Islamic banking